The fertility sparing management of postpartum hemorrhage: A series of 47 cases of Bakri balloon tamponade - İsmet Alkış; Erbil Karaman; Agahan Han; Hasan Cemal Ark; Betül Büyükkaya (Elsevier, 2015)
Objective: To evaluate the success rate of Bakri balloon tamponade (BBT) for managing postpartum hemorrhage (PPH), intractable to conservative medical treatment, as a fertility sparing intervention. Materials and methods: We evaluated 47 women treated with BBT who had severe postpartum hemorrhage and uncontrollable bleeding due to failed treatment with uterotonic agents. The main outcome measure was successful management and preservation of the uterus. Results: Forty-seven women were identified for BBT treatment due to severe PPH. BBT was used to successfully manage hemorrhage in 43 patients, and there was no need for hysterectomy. Four patients required an additional surgical procedure. Of the four failures, a subtotal hysterectomy was performed in two patients, and the other two patients underwent a total hysterectomy. The overall success rate was 91.4%, which was comparable to rates reported earlier. The main cause of PPH was uterine atony (43%). Conclusion: Uterine preservation is an important issue when managing PPH. BBT is an effective, easy to use, and safe procedure for massive PPH that can minimize recourse to hysterectomy after failed medical treatment.